Challenging Ableism: Sexual and Reproductive Health Barriers for Women with Differently Abled Bodies - Zahra, Syeda Abeeha; Noreen, Naveeda; Imran, Abeeha (Biological and Clinical Sciences Research Journal, 2025)
Women with physical disabilities experience compounded marginalization due to ableism, gender inequality, and entrenched socio-cultural norms. These intersecting barriers severely limit their autonomy and access to sexual and reproductive health (SRH) services, particularly in low- and middle-income settings like Pakistan. Objective: To explore the lived experiences and challenges in accessing SRH services among married women with physical disabilities in Lahore, Pakistan. Methods: A qualitative phenomenological study was conducted from January to June 2024 in Lahore, Pakistan. Purposive sampling was used to recruit 15 married women aged 18–40 years with physical disabilities. In-depth semi-structured interviews were conducted in Urdu, audio-recorded, transcribed verbatim, and translated into English. Thematic analysis was performed using NVivo software, following Colaizzi’s seven-step method. The study was grounded in the theoretical frameworks of social constructivism and intersectionality to examine how structural and attitudinal factors shape SRH experiences. Results: Participants reported numerous barriers to accessing SRH services, including negative societal attitudes, discriminatory healthcare practices, inaccessible facilities, and inadequate SRH education. The internalization of stigma, invisibility in SRH discourse, and lack of provider sensitization further marginalized these women. Many participants expressed that health systems neither addressed their specific SRH needs nor considered their lived realities. Conclusion: The study underscores the urgent need to integrate disability-sensitive approaches into SRH policies in Pakistan. Addressing structural ableism, gender discrimination, and socio-cultural bias is critical to ensuring equitable access to SRH services for women with disabilities. A more inclusive health policy framework, provider training, and community awareness are essential to improve SRH outcomes for this underserved population.